Grammatical Competence and Reading Comprehension of Grade 6 Learners - Emmalyn Sola (Journal of Pedagogy and Education Science, 2026)
This study examined the influence of grammatical competence on the reading comprehension of Grade 6 learners at Olas Elementary School, Lagonoy North District, Division of Camarines Sur, for the school year 2024–2025. Specifically, it determined the learners’ levels of grammatical competence and reading comprehension, their correlation, the extent to which grammatical competence influenced reading comprehension, and the design and curricular validity of supplementary materials to improve performance. The study used a descriptive-correlational and research-and-development method, involving 18 Grade 6 learners and 7 master teachers as respondents. Data were gathered using questionnaires and analyzed through Weighted Mean, Standard Deviation, Proficiency Level, Pearson Product-Moment Correlation, and Coefficient of Determination. Findings revealed that learners had a Proficiency Level of 67.08 in grammatical competence and 50.9 in reading comprehension, both under the beginning level. Correlation results showed that noun competence had the strongest and most significant relationship with reading comprehension, while pronouns and prepositions also exhibited weak yet notable correlations. Other grammatical aspects, such as verbs, adverbs, adjectives, and interjections, showed minimal influence. The r² values indicated that nouns had the strongest influence on comprehension skills such as identifying main ideas, supporting ideas, and making inferences. The designed supplementary materials obtained a very high valid rating in both design (3.57) and curricular validity (3.51). The study concluded that grammatical competence had little influence on reading comprehension, though nouns played a modest but meaningful role in learners’ reading understanding.